An Analysis on the Impact of Participatory Budgeting and Procedural Fairness Toward Manager’s Commitment and Performance - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This study aims to test the effect of participatory budgeting and procedural fairness on the manager's commitment and performance either have simultaneous or partial effect. The method of the research used was a survey method that conducted at the pawnshop in North Sumatra with the respondents of the managers in branch offices. The data used is primary data by collecting data through questionnaires. The analysis method used is descriptive-analytical verification. The effect model analyzed by using a structural equation model to analyze the pattern of causal relationships between variables and determine the direct, indirect and total effect of some variables. The results showed that participatory budgeting and procedural fairness simultaneously have a significant and positive effect on the manager’s commitment; participatory budgeting has a significant and positive effect on the manager’s commitment; procedural fairness has a significant and positive effect on the manager’s commitment; participatory budgeting, procedural fairness and manager’s commitment simultaneously has a significant and positive effect on the manager’s performance; the effect of participatory budgeting has a significant and positive effect on the manager’s performance; the procedural fairness has a significant and positive effect on the manager’s performance; the manager’s commitment has a significant and positive effect on the manager’s performance.  Key words : Participatory budgeting, procedural fairness; manager’s commitment, manager’s performance.